A novel computer-aided energy decision-making system improves patient treatment by microwave ablation of thyroid nodule - Du, Rui; Wang, Ranchao; Xu, Hu; Xu, Yuhao; Fei, Zhengdong; Luo, Yifeng; Zhu, Xiaolan; Li, Yuefeng (Computers in biology and medicine, 2025)
The current basis of microwave ablation (MWA) energy use for thyroid nodules (TN) is inadequate, leading to tissue carbonization, which is strongly associated with complications and poor prognosis. This study aims to devise a novel energy decision-making system to improve the subjective use of energy in current MWA procedures. Data from 916 subjects (1364 TN) across three medical centers were collected. In the first two sets, the single-stitch ablation needle energy (ANE) was calculated by analyzing MWA procedure videos. The causes of TN over-ablation (carbonization) were examined, and the relationship between well-ablated TN and ANE was explored based on TN attributes (volume and Young's modulus). Three-dimensional (3D) reconstruction of TN was performed, and a computer-aided model was constructed to optimize the distribution of the ANE field within the 3D-TN. Subsequently, a novel energy decision-making system was developed and tested. The third set was used for external validation. The cause of TN carbonization was found to be related to the overload of ANE with corrected Young's modulus and the selection of mismatched ablation needle power (ANP). A precise ANE model (Model 1) based on well-ablated TN and a needle-placement model (Model 2) based on the 3D-TN and ANP were subsequently constructed. The coupled new energy decision-making system (Model 1 + 2) demonstrated strong clinical generalization capabilities. In conclusion, this novel energy decision-making system can effectively improve the use of MWA energy, significantly promoting the precise treatment of TN. •The mismatched power and energy of the ablation needle leads to nodule carbonization.•The ablation energy matched with nodule Young's modulus can achieve well-ablation.•The novel energy decision-making system can promote the precise ablation of nodule.